2021
DOI: 10.1002/cjce.23964
|View full text |Cite
|
Sign up to set email alerts
|

Composition dependence of cyclohexane‐extracted gangue drying at ambient conditions

Abstract: The drying of residue cyclohexane in a series of reconstituted gangue samples at ambient conditions was studied. The reconstituted gangue samples contained controlled amounts of residual bitumen, water, and fines (solid particles <45 μm). Regardless of the gangue composition, the initial drying flux was constant, and more than 90% of the residual cyclohexane was removed in this stage. The initial drying was driven by the liquid film flow induced by the differences in liquid film's radii of curvature along the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…A rich oil sands ore sample provided by Syncrude Canada Ltd. was used. The ore sample was extracted using cyclohexane (purity 99.0%, certified ACS grade, Fischer Scientific, United States) in a Dean–Stark extraction apparatus . The solvent was condensed in the trap and allowed to overflow back over the sample placed in a thimble, to dissolve and to extract the bitumen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A rich oil sands ore sample provided by Syncrude Canada Ltd. was used. The ore sample was extracted using cyclohexane (purity 99.0%, certified ACS grade, Fischer Scientific, United States) in a Dean–Stark extraction apparatus . The solvent was condensed in the trap and allowed to overflow back over the sample placed in a thimble, to dissolve and to extract the bitumen.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work, we have demonstrated that cyclohexane is probably the most ideal organic solvent to be used for the nonaqueous extraction of bitumen. Also, we have showed how the key gangue compositions affect the effectiveness of removing cyclohexane by an air-drying method under ambient conditions. , The major advantage and drawback of the air-drying method are minimal energy required and being slow, respectively. The process is slow because liquid cyclohexane in the gangue first flows upward due to capillary pressure to the gangue surface before it vaporizes.…”
Section: Introductionmentioning
confidence: 98%